Are Ethical Codes of Conduct Toothless Tigers for Dealing with Employment Discrimination? - Petersen, Lars-Eric 1965-; Krings, Franciska (2009)
This study examined the influence of two organizational context variables, codes of conduct and supervisor advice, on personnel decisions in an experimental simulation. Specifically, we studied personnel evaluations and decisions in a situation where codes of conduct conflict with supervisor advice. Past studies showed that supervisors’ advice to prefer ingroup over outgroup candidates leads to discriminatory personnel selection decisions. We extended this line of research by studying how codes of conduct and code enforcement may reduce this form of discrimination. Eighty German managers evaluated and selected candidates from an applicant pool including Germans (ingroup members) and foreigners (outgroup members). Supervisor advice to prefer ingroup members lowered suitability ratings of outgroup members as well as their chances to be selected for an interview. Ethical codes of conduct referring to equal opportunities limited this form of discrimination, but only when codes were enforced by sanctions and integrated into organizational every-day practice. The implications of these findings for research and practice are discussed.
Keywords: code enforcement; codes of conduct; employment discrimination; Personnel Selection